2013
DOI: 10.1103/physreve.87.012128
|View full text |Cite
|
Sign up to set email alerts
|

Numerical and experimental study of stochastic resistive switching

Abstract: In this paper we study the role of noise in the context of resistive switching phenomena by means of experiments and numerical simulations. Experiments are conducted on a manganite sample. We show that the addition of external Gaussian noise to a small amplitude driving signal yields a contrast ratio between low- and high-resistance states, comparable to that obtained by the application of a large amplitude noiseless signal. Furthermore, excellent agreement between numerical simulation and measurement allows u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
19
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 29 publications
1
19
0
1
Order By: Relevance
“…They found that, under certain conditions, the contrast between lowand high-resistive states is enhanced when some amount of internal noise, inherent to the sample, is present in the system. Recently, experiments on manganite samples have shown that external noise has a beneficial effect during the pulsing protocol [8,9]. As such, the scope of this work is to further study the effect of electrical noise and temperature on a memristive system by means of experimental observation and numerical analysis.…”
mentioning
confidence: 99%
“…They found that, under certain conditions, the contrast between lowand high-resistive states is enhanced when some amount of internal noise, inherent to the sample, is present in the system. Recently, experiments on manganite samples have shown that external noise has a beneficial effect during the pulsing protocol [8,9]. As such, the scope of this work is to further study the effect of electrical noise and temperature on a memristive system by means of experimental observation and numerical analysis.…”
mentioning
confidence: 99%
“…A previous study has indeed shown that the hysteresis of memristive elements can be induced by white noise of appropriate intensity even at very low frequencies of the external driving field 16 . Recently, this prediction was confirmed experimentally 19 . In this work, we consider the circuit shown in Fig.…”
mentioning
confidence: 67%
“…Another source of noise is the input noise that was considered by several authors 16,19 . A previous study has indeed shown that the hysteresis of memristive elements can be induced by white noise of appropriate intensity even at very low frequencies of the external driving field 16 .…”
mentioning
confidence: 99%
“…Introducing linear functions as discussed in this paper allows one to obtain optimal conditions for any device models of memristors. Also, the excellent agreement between simulation 33 and experiment 34 has been reported in the scheme of stochastic resonance. Modulators using memristors have been verified in SPICE simulations.…”
Section: Optimal Condition Of External Voltage Sourcementioning
confidence: 86%